Calculation and Analysis of Stable Operation of Feed water Pumps for Floating Nuclear Power Stations under Marine Conditions. (July 2020) - Cheng, Kun; Wang, Cheng; Fang, Yuan; Wang, Jue
Abstract: Feed water pumps play an important role in floating nuclear power plant system equipment, and their safe and reliable operation directly affects the safety and reliability of the entire power plant. The movement status of floating nuclear power plants under sea conditions will change, and additional inertial forces are generated on the pipelines of the water supply system, which may cause cavitation of the feed water pump. This paper deduces the additional force on the fluid at the inlet pipe of the feed pump under the marine environment, establishes a mathematical model of the fluid flow at the inlet pipe of the feed pump under the influence of ocean conditions, and calculates the stable operation of the feed pump under the ocean conditions once in a century according to the layout plan. The requirements of effective cavitation allowance and necessary cavitation allowance provide theoretical calculation basis for design and layout optimization of feed pumps for floating nuclear power plants.